Study on the relationship between endometrial thickness on the hCG day in the progestin-primed ovarian stimulation protocol and pregnancy outcomes in frozen–thawed embryo transfer cycles - Wang, Yutong; Chang, Yajie; Zhuang, Shaohong; Zeng, Haitao; Liang, Xiaoyan (Frontiers in Endocrinology, 2025)
ObjectiveThe aim of this study was to investigate the relationship between endometrial thickness (EMT) on human chorionic gonadotropin (hCG) day in the progestin-primed ovarian stimulation (PPOS) protocol and pregnancy outcomes in the subsequent frozen–thawed embryo transfer (FET) cycles, providing new insights into embryo transfer strategies for patients undergoing the PPOS protocol.MethodsThis retrospective study included 1,748 patients who underwent the PPOS protocol. Patients were divided into two groups based on the EMT on the hCG day: group A (EMT < 8 mm) and group B (EMT ≥ 8 mm). After 1:1 propensity score matching (group A: n = 701; group B: n = 701), the biochemical pregnancy, clinical pregnancy, and ongoing pregnancy rates were compared. In addition, the pregnancy outcomes under different endometrial preparation protocols were analyzed within each group.Results(1) In groups A and B, the biochemical pregnancy rates were 44.5% and 45.5% (p = 0.707), the clinical pregnancy rates were 38.5% and 42.5% (p = 0.128), and the ongoing pregnancy rates were 29.1% and 34.2% (p = 0.039), respectively. For the cleavage-stage embryo transfers, groups A and B showed no significant differences in the biochemical pregnancy (39.5% vs. 35%, p = 0.285), clinical pregnancy (35.9% vs. 30.5%, p = 0.192), and ongoing pregnancy rates (26.8% vs. 24.4%, p = 0.527). For blastocyst transfers, the biochemical pregnancy (47.8% vs.51.2%, p = 0.307) was similar, but, clinical pregnancy (40.2% vs. 49%, p = 0.009), and ongoing pregnancy rates (30.6% vs. 39.6%, p = 0.005) were significantly higher in group B. (2) In group A, the endometrial preparation protocols had no statistically significant effect on the pregnancy outcomes. However, the natural cycles showed potentially better results (biochemical pregnancy rate, 43.1%; clinical pregnancy rate, 40.0%; and ongoing pregnancy rate, 34.1%) than hormone replacement therapy (HRT) (44.1%, 38.6%, and 29.9%, respectively), gonadotrophin-releasing hormone agonist plus HRT (GnRH-a+HRT) (45.1%, 39.3%, and 26.3%, respectively), and the mild stimulation cycles (27.8%, 16.7%, and 11.1%, respectively). In group B, patients using the GnRH-a+HRT protocol showed higher biochemical pregnancy (53.5%, p = 0.022), clinical pregnancy (48.7%, p = 0.096), and ongoing pregnancy rates (40.4%, p = 0.032) compared with those on natural cycles (38.2%, 33.9%, and 25.2%, respectively), HRT (42.9%, 40.8%, and 33.8%, respectively), and the mild stimulation protocol (45.5%, 45.5%, and 27.3%, respectively).ConclusionsThe EMT on the hCG day in the PPOS cycle was positively related to the pregnancy outcomes of subsequent FET, with EMT ≥8 mm associated with better pregnancy outcomes, particularly in patients undergoing blastocyst transfers.